2008
DOI: 10.1007/bf03326056
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of chikusaku-eki and mokusaku-eki and its inhibitory effect on sapstaining fungal growth in laboratory scale

Abstract: Chikusaku-eki and Mokusaku-eki are natural resources and acidic liquid by-products of bamboo and broad leaved trees charcoal burner. These products contain more than 200 ingredients, including phenols, poly phenols and acetic acids. These by-products were tested for their fungicidal activity against sapstaining fungi. There are no studies about the antifungal activity of Chikusaku-eki and Mokusaku-eki against wood staining fungi in the literature. According to the recent findings, this is the first report abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 25 publications
0
26
0
2
Order By: Relevance
“…This strongly suggests that polyphenolic compounds affect the antifungal activity in addition to the previously reported acidic nature of wood vinegar (Velmurugan et al 2009). Nonetheless, mold can be removed easily by surfacing or planing, and does not discolor wood as severely as sapstain.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…This strongly suggests that polyphenolic compounds affect the antifungal activity in addition to the previously reported acidic nature of wood vinegar (Velmurugan et al 2009). Nonetheless, mold can be removed easily by surfacing or planing, and does not discolor wood as severely as sapstain.…”
Section: Resultsmentioning
confidence: 55%
“…As alternatives, various natural products, such as plant essential oils (e.g., cedar leaf) and wood vinegar (Dawson-Andoh et al 2000), are being investigated, although currently these are not being produced commercially. Previous studies (Sulaiman et al 2005;Velmurugan et al 2009) have demonstrated that the presence of acids (mainly acetic acid) and phenols in wood vinegar made from bamboo and broad-leaved trees have antifungal properties useful to treat wood. Although Ikergami et al (1992) showed that wood vinegar, which contains guaiacol, cresol, 4-ethyl-2-methoxyphenol, and 2, 6-dimethoxyphenol, has good antifungal activity, there is, in general, very little scientific evidence regarding the antifungal properties of wood vinegar.…”
Section: Introductionmentioning
confidence: 99%
“…Velmurugan and co-authors [38,39] have published scientific evidence that wood vinegar made from bamboo and broad leaved trees were effective against sapstaining fungi at minimum concentrations (0.10-1.0%). Results revealed that compounds of Chikusaku-eki and Mokusaku-eki markedly inhibited fungal growth but the exact mode of action of active compounds need to be studied further.…”
Section: Wood Preservativementioning
confidence: 99%
“…Many control technologies have been developed to inhibit fungi that cause discolouration on timber. It has been shown (Velmurugan et al 2009) that wood vinegar made from bamboo and broad-leaved trees is effective against sapstaining fungi. The results revealed that compounds of Chikusaku-eki and Mokusaku-eki markedly inhibit fungal growth and the product possesses both antifungal and antioxidant properties as well as potential for use as a natural preservative in woodworking industries.…”
Section: Use Of Pyrolysis Liquids As a Fungicidementioning
confidence: 99%